(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The simile construction is one of the valuable conclusions of the existing researches in linguistics, as well as the issues which are continuously studied and perfected on the basis of new scientific and theoretical views. It should be stressed that the development of linguistics based on today’s anthropocentric paradigm has opened the way to research similes not only lexically, grammatically, but also pragmatically. In this case, the research of the simile construction in relation to language and speech stage allows to describe its new features. Therefore, the system of lexicology and today’s semasiology requires the research of the structure of analogy and its members from a new point of view. Therefore, it is important to study this phenomenon in the framework of new theoretical perspectives at the stage of language and speech.